A feature interaction conflicts detection engine for pervasive networked environment - Low, H. K.; Chieng, D.; Mustapha, A. K.; Ngeow,, Y. C.; Goh, E. (2007)
Feature interaction (FI) problems have long been a popular topic of investigation in Internet telephony environment. Due to recent proliferation of ubiquitous networked appliances, FI problems in networked appliances environment are becoming more apparent. FI problems create various conflicts which hinder system performance in term of efficiency. While most of the F! related research works are concentrating on networked appliances or Internet telephony environment, we propose a cache approach to detect FI problems and conflicts in both environments. This approach caches context information from context storage hence, offers more efficient and faster conflict detection in dynamic context environment. This paper will later provides an analysis of this conflict detection algorithm.